Musical Hearing and Musical Experience in Second Language English Vowel Acquisition - Jekiel, Mateusz; Malarski, Kamil (American Speech-Language-Hearing Association, 2021)
Purpose: Former studies suggested that music perception can help produce certain accentual features in the first and second language (L2), such as intonational contours. What was missing in many of these studies was the identification of the exact relationship between specific music perception skills and the production of different accentual features in a foreign language. Our aim was to verify whether empirically tested musical hearing skills can be related to the acquisition of English vowels by learners of English as an L2 before and after a formal accent training course. Method: Fifty adult Polish speakers of L2 English were tested before and after a two-semester accent training in order to observe the effect of musical hearing on the acquisition of English vowels. Their L2 English vowel formant contours produced in consonant–vowel–consonant context were compared with the target General British vowels produced by their pronunciation teachers. We juxtaposed these results with their musical hearing test scores and self-reported musical experience to observe a possible relationship between successful L2 vowel acquisition and musical aptitude. Results: Preexisting rhythmic memory was reported as a significant predictor before training, while musical experience was reported as a significant factor in the production of more native-like L2 vowels after training. We also observed that not all vowels were equally acquired or affected by musical hearing or musical experience. The strongest estimate we observed was the closeness to model before training, suggesting that learners who already managed to acquire some features of a native-like accent were also more successful after training. Conclusions: Our results are revealing in two aspects. First, the learners' former proficiency in L2 pronunciation is the most robust predictor in acquiring a native-like accent. Second, there is a potential relationship between rhythmic memory and L2 vowel acquisition before training, as well as years of musical experience after training, suggesting that specific musical skills and music practice can be an asset in learning a foreign language accent.